Efficacy of sildenafil and high-dose anakinra in an MIS-C patient with pulmonary vasculitis: A case report - La Torre, Francesco; Calabrese, Gerolmina; Signorile, Katia; Bizzoco, Francesca; Mastrorilli, Carla; Strippoli, Antonella; Amato, Doriana; Carella, Francesco; Vairo, Ugo; Giordano, Paola; Milella, Leonardo; Cardinale, Fabio (Frontiers in Pediatrics, 2023)
Multisystem inflammatory syndrome in children (MIS-C) is a newly identified clinical entity still not very well known in terms of epidemiology, pathogenesis, and long-term outcome. Pulmonary involvement with acute respiratory failure (ARF) is an unusual life-threatening complication of MIS-C, often reason for admission to Pediatric Intensive Care Unit (PICU) and use of mechanical ventilation (1,2). We present a case of a seven-year-old male patient, previously healthy, hospitalized for MIS-C, treated with intravenous immunoglobulins (IVIG), high dose methylprednisolone and anakinra. After two days of aforementioned therapy, the patient presented hypoxia (SatO2: 85% in ambient air room) and breath difficulty. A chest computed tomography (CT) showed the presence of multiple bilateral basal parenchymal thickening and small basal pleural effusion and an arterial blood gas analysis revealed severe hypoxia (PaO2/FiO2 ratio 170 mmHg). Because of worsening of respiratory distress, the patient was therefore transferred to PICU, where invasive mechanical ventilation and continuous infusion of anakinra (12 mg/kg/day) were started. An echocardiogram was performed which showed an increase in pulmonary pressure (40 mmHg) with normal heart ejection fraction (55%) and the hypothesis of pulmonary vasculitis involving the pulmonary arterioles was made. Therefore, therapy with sildenafil (0.15 mg/kg/day) was promptly set up, with immediate improvement of the clinical picture of respiratory failure, reduction of pulmonary pressure (23 mmHg) and subsequent extubation at 36 hours with regular clinical course until discharge. Conclusion: As far as we know, our case represents the first report of pulmonary vasculitis in MIS-C patient. The use of sildenafil and high-dose continuous anakinra may represent a rescue therapy in cases of MIS-C with pulmonary vasculitis or with difficulty in extubation, allowing short time hospitalization in intensive care and improving long-term outcome in these patients.